Hubungan Antara Gaya Kepemimpinan Kepala Sekolah Terhadap Efektivitas Supervisi di Sekolah Menengah Kejuruan (SMK) - Marfuah, Marfuah; Sururi, Sururi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
This study aims to analyze the relationship between the principal's leadership style and the effectiveness of supervision in Vocational High Schools (SMK). The research method used is a quantitative approach with a correlational design. The research sample consisted of 100 vocational school teachers who were randomly selected from five vocational schools in City Bandung Barat. Data were collected using questionnaires on the principal's leadership style and the effectiveness of supervision that had been tested for validity and reliability. Data analysis used Pearson correlation techniques and simple linear regression. The results showed that there was a significant positive relationship between the principal's leadership style and the effectiveness of supervision (r = 0.78; p < 0.05). The transformational leadership style had the strongest correlation with the effectiveness of supervision (r = 0.82; p < 0.05), followed by the democratic leadership style (r = 0.75; p < 0.05), and the autocratic leadership style (r = 0.68; p < 0.05). The results of the regression analysis showed that the principal's leadership style contributed 60.8% to the effectiveness of supervision. These findings emphasize the importance of the principal's leadership style in improving the effectiveness of supervision in vocational schools.